Validasi Dan Kepraktisan Perangkat Pembelajaran Berbasis PJBL untuk Memberdayakan Hasil Belajar Pada Materi Sistem Reproduksi Manusia Kelasa XI SMAS Bina Utama Pontianak - Utin Dini Zahira Shofa Dini; Eka Trisianawati; Herditiya (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
Twenty-first-century education requires learning that promotes students’ active engagement and improves learning outcomes through innovative instructional approaches. However, students’ achievement in the Human Reproductive System topic remains low because the material is considered complex, while teachers have not optimally implemented Project-Based Learning (PjBL) or integrated learning devices. This study aimed to develop PjBL-based learning devices for the Human Reproductive System topic for Grade XI students at SMAS Bina Utama Pontianak and to determine their validity and practicality. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants included expert validators, a biology teacher, and 33 Grade XI students. Data were collected through observations, interviews, questionnaires, tests, and documentation, and analyzed descriptively using percentage-based validity and practicality criteria. The developed learning devices consisted of teaching modules, teaching materials, student worksheets (LKPD), learning media, and assessment instruments. The validation results indicated that the learning devices were highly valid, with media validation reaching 94.08% and material validation 91.17%. Practicality testing also showed highly practical criteria, with student response scores of 83.00% in the small-scale trial and 83.61% in the large-scale trial. Therefore, the developed PjBL-based learning devices are highly valid and practical and are suitable for supporting biology learning to improve students' learning outcomes on the Human Reproductive System topic.